The use of cognitive behaviour therapy in the management of BPSD in dementia (Innovative practice). (February 2018) - Koder, Deborah
Psychosocial approaches to the management of behavioural and psychological symptoms of dementia have received much support in the scientific literature. The following paper focuses on cognitive behaviour therapy as a valid framework in assessing and treating people with behavioural and psychological symptoms of dementia. The importance of identifying symptoms of depression and anxiety is emphasized, as cognitive behaviour therapy has been shown to be an effective intervention for these conditions in older adults. Modifications of cognitive behaviour therapy for those with dementia are discussed based on available evidence, with emphasis on incorporating nursing home staff in treatment programs and focusing on behavioural elements of cognitive behaviour therapy such as activity scheduling. The paper concludes with suggestions regarding how to incorporate and promote the use of cognitive behaviour therapy in dementia care settings.